ANALISIS FAKTOR PENYEBAB KEBAKARAN HUTAN DAN LAHAN SERTA UPAYA PENCEGAHAN YANG DILAKUKAN MASYARAKAT DI KECAMATAN BASARANG KABUPATEN KAPUAS KALIMANTAN TENGAH - Aditiea Loren; Muhammad Ruslan; Fadly H. Yusran; Fonny Rianawati (Universitas Lambung Mangkurat, 2015)
This study aims to identify the causes, prevention, and analyze the characteristics of the relationship with the peoples of the community efforts around the scene of the fire. The samples were the people residing in the District Basarang taken using Slovin formula with 10 % percent inaccuracy. In identifying the causes of the fire based on what is know to the respondents while prevention efforts using parameters : the creation of firebreaks, clean the fuel under forest stands/land, controlled burning and noticed the burning time. Characteristics of respondents to prevention using three characteristics such as age, education and occupation. The results showed that the fires in the District Basarang caused by agricultural land clearing by burning, throwing cigarette butts carelessly, the presence of fuel/dry combustible materials, sparks coming from the region and due to natural factors such as long dry season. Efforts to prevent fires by creating firebreaks dominated 88.8%, clean the fuel under forest stands/land 72.4%, conduct controlled burn 71.4%, and 53.1% of the time of burning. The variables of age, education, and community work towards making firebreaks and burning have a relationship that is being controlled. The variables of age, education, and community work against efforts to clean the fuel under forest stands/land and of the time of combustion have a pretty strong and powerful